A special kind of neighborhood - Waring, Rob; National Geographic Society (U.S.); Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
Most cities have local areas called'neighbourhoods.' The mission district is one of San Francisco's oldest neighbourhoods. Many people think it's very special because it's so multi-cultural. What makes the mission district so multi-cultural? Why does that make it special?
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography